Keadilan Prosedural dan Keadilan Distributif sebagai Prediktor Employee Engagement - Meily Margaretha; T. Elisabeth Cintya Santosa (Jurnal Manajemen Maranatha, 2012)
This study examined the predictors of two types of employee engagement: job engagement and organizational engagement. The effect of justice perceptions (procedural and distributive justice) on various outcomes might be due in part to employee engagement. In other words, when employees have high perceptions of justice in their organization, they are more likely to feel obliged to be fair in how they perform their roles by giving more of themselves through greater levels of engagement. On the other hand, low perceptions of fairness are likely to cause employees to withdraw and disengaged themselves from their work roles. The samples of the research are 32 lecturers in Departement Management Economic Faculty, Maranatha Christian University Bandung by purposive sampling. The examination utilizes with Linier Regression Analysis. The result of this research showed that procedural and distributive justice predicts employee engagement (job engagement and organizational engagement).